Globule and fiber formation with elastin-like polypeptides: a balance of coacervation and crosslinking. Issue 16 (11th April 2022) - Lau, Kirklann; Reichheld, Sean; Sharpe, Simon; Cerruti, Marta
Abstract : The timing of crosslinking relative to coacervation controls elastin droplet morphology and propensity for forming interconnected droplet networks. We explore this relationship with an elastin-like peptide (ELP) and genipin crosslinker model. Abstract : Elastic fiber assembly is a complex process that requires the coacervation and cross-linking of the protein building block tropoelastin. To date, the order, timing, and interplay of coacervation and crosslinking is not completely understood, despite a great number of advances into understanding the molecular structure and functions of the many proteins involved in elastic fiber assembly. With a simple in vitro model using elastin-like polypeptides and the natural chemical crosslinker genipin, we demonstrate the strong influence of the timing and kinetics of crosslinking reaction on the coacervation, crosslinking extent, and resulting morphology of elastin. We also outline a method for analyzing elastin droplet network formation as a heuristic for measuring the propensity for elastic fiber formation. From this we show that adding crosslinker during peak coacervation dramatically increases the propensity for droplet network formation.